Recurrent Hemolytic and Uremic Syndrome Induced by Escherichia Coli. Issue 1 (January 2016) - Commereuc, Morgane; Weill, Francois-Xavier; Loukiadis, Estelle; Gouali, Malika; Gleizal, Audrey; Kormann, Raphaël; Ridel, Christophe; Frémeaux-Bacchi, Véronique; Rondeau, Eric; Hertig, Alexandre
Abstract : Abstract: A widespread belief is that typical hemolytic and uremic syndrome (HUS) does not recur. We report the case of a patient infected twice with raw milk taken from his own cow and containing a Shiga toxin–producing Escherichia coli O174:H21 that induced recurrent HUS causing severe renal and cerebral disorders. A genomic comparison of the human and bovine Shiga toxin–producing Escherichia coli O174:H21 isolates revealed that they were identical. Typical HUS may recur. Since milk from this animal was occasionally distributed locally, thereby posing a serious threat for the whole village, this particular cow was destroyed.